lncRNA DLEU1 Modulates Proliferation, Inflammation, and Extracellular Matrix Degradation of Chondrocytes through Regulating miR-671-5p - Xiangkun Wu; Shuai Yin; Lihua Yan; Yongxi Liu; Lilin Shang; Jun Liu (Journal of Immunology Research)
Long noncoding RNAs (lncRNAs) have been shown to be involved in the development of osteoarthritis. However, the expression, function, and mechanism of DLEU1 in OA development remain largely unclear. The present reference demonstrates that DLEU1 is overexpressed in OA specimens compared to control cartilages. Inflammatory cytokines IL-1β, TNF-α, and IL-6 induce DLEU1 expression in chondrocytes. Ectopic expression of DLEU1 induces chondrocyte proliferation, degradation of ECM, and inflammation mediators such as IL-6, IL-8, and TNF-α secretion. Moreover, we demonstrated that DLEU1 targets miR-671-5p expression in chondrocytes. Overexpression of DLEU1 suppresses miR-671-5p expression in chondrocytes. The expression of miR-671-5p is decreased in OA specimens compared to control cartilages. There is a negative correlation between the expression of miR-671-5p and DLEU1 in OA specimens. Inflammatory mediators IL-1β, TNF-α, and IL-6 suppress miR-671-5p expression in OA specimens. Elevated expression of miR-671-5p suppresses chondrocyte proliferation, degradation of ECM, and secretion of inflammation mediators. DLEU1 overexpression promotes chondrocytes proliferation, degradation of ECM, and secretion of inflammation mediators via regulating miR-671-5p. These results suggested that DLEU1 acts as one destructive role in OA development via regulating miR-671-5p.